Rainfall‐Runoff Modeling in Rocky Headwater Catchments for the Prediction of Debris Flow Occurrence - Bernard, Martino; Barbini, Matteo; Berti, Matteo; Boreggio, Mauro; Simoni, Alessandro; Gregoretti, Carlo (Water resources research, 2025)
In the Dolomites, steep rocky cliffs are marked by numerous narrow gullies. When high‐intensity short‐duration precipitation occurs, these gullies concentrate and direct surface runoff to the screes at the foot of rock cliffs. Surface runoff mixes with loose sediments, creating a solid‐liquid surge that, as it moves downhill, increases its volume entraining debris material and transforms into a granular debris flow. Given the ongoing challenge of modeling the relationship between intense rainfall, surface runoff, and debris flow initiation, we take advantage of data from three monitoring stations operating in distinct debris flow active catchments in our study area to make progress. These stations, strategically positioned close to debris flows initiation zones, record videos and different types of flow‐stage data, helping us pinpoint the timing and form of incoming discharge hydrographs. Over a 15‐year period of observation, we collected a comprehensive data set on runoff and mass movement in these catchments, offering valuable insights into their hydrological behavior and the initiation of granular debris flows. To compute infiltration excess runoff generation, we refined an already existing hydrological model and calibrated it using discharge measured at one of the monitoring stations. Testing this updated model against observations from two other larger debris flow sites showed that it can reproduce the initial phases of a debris flow, when sediment concentration rapidly rises. These findings suggest that a well‐tuned hydrological model can predict the discharge from intense, short rainfall events that typically trigger debris flows, as well as the early stages of these phenomena. Plain Language Summary In the Dolomites (Eastern Italian Alps), during summer thunderstorms, narrow gullies on steep rocky cliffs channel water to loose sediments at the foot of the cliffs. Water mixed with loose debris creates a powerful solid‐liquid surge that, moving downhill, turns into a debris flow. Predicting debris flows is challenging due to the complex relationship between heavy rain, water discharge, and sediment movement. However, it is crucial because many human infrastructures are built on debris flow fans. To understand the triggering of debris flows, we used data from three monitoring stations installed in areas where debris flows often start. These stations include various instruments that record videos and different types of water flow data. The significant amount of data recorded over 15 years concerning surface discharge and the initiation of debris flows enabled us to test, refine and calibrate an existing model designed to simulate these processes. Testing this model with data from two other sites showed it could predict the early stages of a debris flow, reproducing the shape and timing when the flow increases quickly. This suggests that a well‐calibrated model can forecast both water runoff from intense short rains and the initial phases of debris flows. Key Points Rainfall and flow monitoring stations to study hydrology of 3 bedrock‐dominated catchments prone to debris flows in the Dolomites (Italy) Runoff measured by a sharp‐crested weir near a debris‐flow initiation site used to calibrate and test an event‐based rainfall‐runoff model The calibrated model satisfactorily approximates the initial phase of stage hydrographs recorded during storms that triggered debris flows